2007
DOI: 10.1021/bm060376q
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Cellulose Regeneration from Cellulose−NaOH−Water Gels and Comparison with Cellulose−N-Methylmorpholine-N-Oxide−Water Solutions

Abstract: The regeneration kinetics of cellulose from cellulose--NaOH--water gels immersed in a nonsolvent bath is studied in detail. Cellulose concentration, bath type, and temperature were varied, and diffusion coefficients were determined. The results were compared with data measured and taken from the literature on the regeneration kinetics of cellulose from cellulose--N-methylmorpholine-N-oxide (NMMO) monohydrate solutions. Different theories developed for the transport behavior of solutes in hydrogels or in porous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 35 publications
7
58
0
Order By: Relevance
“…This indicates that the incorporation of CO 2 into cellulose under the conditions studied is reversible and not PRC pre-treated regenerated cellulose (ethanol) favoured when the alkalinity of the system is decreased by the extensive addition of water, which is a behaviour (reported as hydrolysability) expected of alkyl carbonates when brought into aqueous conditions (Franchimont 1910). Regeneration with ethanol, on the other hand, can be assumed to facilitate a fast aggregation of cellulose chains, as it has been shown that dissolved cellulose contracts strongly in alcohol when compared to water (Gavillon and Budtova 2007). This strong contraction could then be the reason for ethanol being able to preserve the chemisorbed CO 2 i.e.…”
Section: Chemical Structures Of Dissolved and Regenerated Cellulosementioning
confidence: 99%
“…This indicates that the incorporation of CO 2 into cellulose under the conditions studied is reversible and not PRC pre-treated regenerated cellulose (ethanol) favoured when the alkalinity of the system is decreased by the extensive addition of water, which is a behaviour (reported as hydrolysability) expected of alkyl carbonates when brought into aqueous conditions (Franchimont 1910). Regeneration with ethanol, on the other hand, can be assumed to facilitate a fast aggregation of cellulose chains, as it has been shown that dissolved cellulose contracts strongly in alcohol when compared to water (Gavillon and Budtova 2007). This strong contraction could then be the reason for ethanol being able to preserve the chemisorbed CO 2 i.e.…”
Section: Chemical Structures Of Dissolved and Regenerated Cellulosementioning
confidence: 99%
“…The understanding of the mechanisms governing regeneration kinetics opens the ways in controlling final cellulose morphology. That is why we started to study the regeneration kinetics of cellulose from cellulose-8% NaOH-water gelled solutions (Gavillon and Budtova 2007). It was shown that regeneration in pure water is diffusion-controlled (Fick approach); NaOH diffusion coefficients were determined as a function of cellulose concentration and bath temperature.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, the higher the bath temperature, the quicker the NaOH/thiourea/urea/H 2 O released from cellulose samples, and thus the quicker cellulose regeneration. The same occurred for the regeneration of 3% Solucell/NMMO solutions in water baths of different temperatures [9]. Tab.…”
Section: The Effect Of Cellulose Concentration On the Coagulation Promentioning
confidence: 73%
“…On the other hand, too high coagulation concentration could be not only capable of facilitating decomposition of cellulose but also mainly responsible for an increase of the pore size of the fibers, so 1.5 mol/l H 2 SO 4 was found to be the most effective coagulant in our experiments. When cellulose was dissolved in NaOH/H 2 O solution, the results from the literature indicated a different case, cellulose/NaOH/H 2 O gels were contracting more than twice in methanol baths [9]. In most of the cases, the fastest contraction occurs during the first 10-20 seconds after sample immersion into the regenerating bath; during the following 30-40 seconds the sample slowly approaches its equilibrium size.…”
Section: The Effect Of Coagulation Concentration and Time On Boundarymentioning
confidence: 99%
See 1 more Smart Citation